Frequency and Predictors of Dysphagia in Patients With Recent Small Subcortical Infarcts. Issue 1 (January 2017) - Fandler, Simon; Gattringer, Thomas; Eppinger, Sebastian; Doppelhofer, Kathrin; Pinter, Daniela; Niederkorn, Kurt; Enzinger, Christian; Wardlaw, Joanna M.; Fazekas, Franz
Abstract : Background and Purpose—: Detailed data on the occurrence of swallowing dysfunction in patients with recent small subcortical infarcts (RSSI) in the context of cerebral small vessel disease are lacking. This prompted us to assess the frequency of and risk factors for dysphagia in RSSI patients. Methods—: We identified all inpatients with magnetic resonance imaging–confirmed RSSI between January 2008 and February 2013. Demographic and clinical data were extracted from our stroke database, and magnetic resonance imaging scans were reviewed for morphological changes. Dysphagia was determined according to the Gugging Swallowing Screen. Results—: We identified 332 patients with RSSI (mean age, 67.7±11.9 years; 64.5% male). Overall, 83 patients (25%) had dysphagia, which was mild in 46 (55.4%), moderate in 26 (31.3%), and severe in 11 patients (13.3%). The rate of dysphagia in patients with supratentorial RSSI was 20%. Multivariate analysis identified a higher National Institutes of Health Stroke Scale score ( P <0.001), pontine infarction ( P <0.01), and more severe white matter hyperintensities (Fazekas grades 2 and 3, P =0.03) as risk factors for swallowing dysfunction. Conclusions—: Dysphagia is present in a quarter of patients with RSSI and has to be expected especially in those with higher stroke severity, pontine infarction, and severe white matter hyperintensities. Abstract : Supplemental Digital Content is available in the text.